2022
DOI: 10.1101/2022.06.27.497849
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mex67 paralogs mediate division of labor in trypanosome RNA processing and export

Abstract: In opistokhonts (animals and fungi), mRNA export to the cytoplasm is mediated by the Mex67/Mtr2 (NXF1/NXT1) heterodimer via the nuclear pore complex (NPC). In contrast to most nucleocytoplasmic transport, mRNA export requires ATP-dependent remodeling machinery, and in animals and fungi is Ran-independent. While most eukaryotes possess one Mex67 gene, trypanosomes have three distinct Mex67 paralogs, while retaining a single Mtr2 gene. We show here that these paralogs, TbMex67, TbMex67b and TbMex67L, have differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 96 publications
0
12
0
Order By: Relevance
“…5 B ), (ii) Tb927.6.890, unique to kinetoplastida, but possessing a SAC3/GANP/THP3 domain at its N terminus; Sac3 from yeast is a well-known interactor of MEX67-Mtr2 that localizes to the cytoplasmic side of the NPC ( 36 ), (iii) Tb927.7.2330 and Tb927.11.5560, two proteins of unknown function, and finally (iv) Tb927.10.7680, a GTPase-activating protein (RabGAP-TBC domain, TBC-RootA ( 37 )); TBC-RootA is likely involved in the GTP-dependent mRNA transport via the small GTPase Ran ( 11 ). Ran, Ran-binding protein, and MEX67b ( 38 ), all high-confidence interactors in the pulldown, were also enriched in the BioID PPI dataset but below a significance cutoff. Two further proteins common to both BioID and pulldown are cyclophilin (localization to the nucleolus, unknown function) and KMP11 (a protein of the basal body and flagellum attachment zone) ( 20 , 39 ), both likely contaminants.…”
Section: Resultsmentioning
confidence: 98%
“…5 B ), (ii) Tb927.6.890, unique to kinetoplastida, but possessing a SAC3/GANP/THP3 domain at its N terminus; Sac3 from yeast is a well-known interactor of MEX67-Mtr2 that localizes to the cytoplasmic side of the NPC ( 36 ), (iii) Tb927.7.2330 and Tb927.11.5560, two proteins of unknown function, and finally (iv) Tb927.10.7680, a GTPase-activating protein (RabGAP-TBC domain, TBC-RootA ( 37 )); TBC-RootA is likely involved in the GTP-dependent mRNA transport via the small GTPase Ran ( 11 ). Ran, Ran-binding protein, and MEX67b ( 38 ), all high-confidence interactors in the pulldown, were also enriched in the BioID PPI dataset but below a significance cutoff. Two further proteins common to both BioID and pulldown are cyclophilin (localization to the nucleolus, unknown function) and KMP11 (a protein of the basal body and flagellum attachment zone) ( 20 , 39 ), both likely contaminants.…”
Section: Resultsmentioning
confidence: 98%
“…Since this paper was accepted, Obado et al (2022) have demonstrated that the protein encoded by Tb927.11.2340, which was strongly and specifically pulled down with DRBD18, is a functional MEX67 paralog.…”
Section: Note Added In Proofmentioning
confidence: 95%
“…Few FG-Nup PPIs were identified (4/9 FG-Nups) (here and [ 29 ]) and where identified are restricted to multi-complex FG-Nups attached to the outer ring or a component of the outer ring itself [ 29 ]. Additionally, only a single PPI was identified between a LAP (LAP333) and the export system(1/3) [ 29 , 145 ], which is consistent with a location at the membrane ring and not the transport channel.…”
Section: Resultsmentioning
confidence: 83%